ERI SILK WORM REARING ON DIFFERENT CASTOR GENOTYPES AND THEIR ECONOMIC ANALYSIS - RAJASRI MANDALI; V. LAKSHMI NARAYANAMMA (The Bioscan, 2015)
Eight castor genotypes viz., Haritha, Kiran, Kranthi, PCS- 262, PCH-111, PCH-222, GCH-4 and DCH-177 were evaluated to identify suitable castor genotypes and the level of defoliation of castor leaves and their performance for rearing eri silk worm, Samia cynthia ricini. The castor genotypes PCH-111, PCS 262 and GCH-4 were found to be promising with respect to rearing performance indicators and Cocoon traits of Eri silkworm. Leaf defoliation studies indicated that the castor leaves can be removed up to 30% and can be used for Eri silk worm rearing. Significant differences were recorded with the rearing and grainage parameters of Eri silk worm fed with different castor genotypes. Castor hybrid, PCH 111 was found to be superior to other genotypes in improving the rearing performance of eri silk worm with maximum records of mature larval weight (1.85 g), cocoon weight (2.02 g ), pupal weight(1.62 g ), Shell weight ( 0.45 g), silk ratio (22.27%) and shorter larval period (19days). The Eri silk yield was also significantly highest with worms fed with PCS-262 castor leaves (12.85 kg/ha) followed by PCH- 111 (12.3 kg/ha) and GCH- 4 (12.25 kg/ha). Castor genotypes viz., PCH-111, PCS 262 and GCH-4 can be grown for dual purpose which gives additional returns of about Rs.4000/- to 5000/- per ha due to ericulture for the resource poor farmers of Southern Telangana region. Higher C: B ratio was realized with castor hybrid PCH-111 (1:2.80) followed by PCS-262 (1:2.77) and GCH-4 (1:2.65). Hence, these castor hybrids / genotypes were recommended to future research and development endeavors of integrated eri silkworm rearing along with castor seed production.